Iman Yang Sejati Mengubah Rintangan Menjadi Kebahagiaan (Yakobus 1:2) - Iswan Garamba; Abad Jaya Zega (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
This article focuses on the concept of authentic faith in the Christian context, discusses suffering, and explores how faith influences the way an individual confronts life's challenges. Genuine Christian faith is portrayed as a belief that goes beyond the intellectual realm and is reflected in a person's daily actions. The Letter of James emphasizes the importance of facing suffering with joy and how it tests one's faith and endurance. Suffering is described as a test that can examine and strengthen a person's faith. It is seen as a consequence of humanity's fall into sin but is also considered a part of God's salvation plan. Through suffering, God's compassion for humanity is revealed, and suffering becomes an essential element in spiritual growth and maturity. Strong faith, endurance, and patience help transform suffering into happiness. Furthermore, the article delves into the theological perspectives and historical context of the Letter of James, as well as James' efforts to correct misconceptions about the nature of faith that saves a person. Overall, the article provides deep insights into the concept of genuine faith and how faith can impact the way individuals confront challenges and attain true happiness in Christ.